Inhibition properties of propolis extracts to some clinically important enzymes. (1st November 2016) - Baltas, Nimet; Yildiz, Oktay; Kolayli, Sevgi
Abstract: The present study was conducted to envisage inhibition effects of propolis on the crucial enzymes, urease, xanthine oxidase (XO) and acetylcholinesterase (AChE). Some of the antioxidant properties of the propolis samples were determined using the total phenolic content (TPE) and total flavonoids in the eight different ethanolic propolis extracts (EPE) samples. Inhibition values of the enzymes were expressed as inhibition concentration (IC50 ; mg/mL or μg/mL) causing 50% inhibition of the enzymes with donepezil, acetohydroxamic acid and allopurinol as reference inhibitors. All the propolis extracts exhibited variable inhibition effects on these enzymes, but the higher the phenolic contents the lower the inhibitions values (IC50 = 0.074 to 1.560 mg/mL). IC50 values of the P5 propolis sample having the highest TPE, obtained from Zonguldak, for AChE, urease and XO were 0.081 ± 0.009, 0.080 ± 0.006 and 0.074 ± 0.011 μg/mL, respectively. The EPE proved to be a good source of inhibitor agents that can be used as natural inhibitors to serve human health.